Pemberdayaan Ekonomi Ikatan Pelajar Nahdlatul Ulama Melalui Komplongisasi di Desa Bekiring - Mega Putri Aulia; Hanafi Hadi Susanto (Social Science Academic, 2023)
This study aims to find out how the strategy for implementing the complementary activities, how the methods used in the complementary activities. The method used in this study is the ABCD (Asset Based Community Driven-Development) method in the form of proper guidance and direction of activities. The results of the study show that the provision of public facilities can be realized through mutual cooperation which is reflected in the grouping activities. The conclusion from this study is that komplongisasi is one of the efforts to provide capital for community activities such as fees for garbage, street lights and various other joint fees. Komplongisasi also shows the traditions of the village community who continue to uphold mutual cooperation, togetherness and helping each other. By holding the komplongisasi tradition, several benefits are obtained, namely helping residents who have economic deficiencies, improving public facilities. Through the implementation of this activity, it can increase the independence of citizens to be able to meet the needs of residents, one of which is development through community self-help. The program for making compounding in Bekiring Village can run smoothly, along with the enthusiasm of the residents who take part in this program.